Historical sea ice data - Christie, Katherine; Hollmen, Tuula; Flint, Paul; Douglas, David (Dryad Digital Repository, 2018)
This file contains observed sea ice concentrations extracted for the core SPEI wintering area from daily gridded (25 km resolution) estimates that were derived from passive microwave satellite imagery using the Bootstrap Algorithm and disseminated by the National Snow and Ice Data Center, Boulder, CO. Data Citations: (1) Comiso, J. C. 2017. Bootstrap Sea Ice Concentrations from Nimbus-7 SMMR and DMSP SSM/I-SSMIS, Version 3. Boulder, Colorado USA. NASA National Snow and Ice Data Center Distributed Active Archive Center. doi: https://doi.org/10.5067/7Q8HCCWS4I0R. (2) Cavalieri, D. J., C. L. Parkinson, P. Gloersen, and H. J. Zwally. 1996, updated yearly. Sea Ice Concentrations from Nimbus-7 SMMR and DMSP SSM/I-SSMIS Passive Microwave Data, Version 1. Boulder, Colorado USA. NASA National Snow and Ice Data Center Distributed Active Archive Center. doi: https://doi.org/10.5067/8GQ8LZQVL0VL.